Post-Fire Behavior of Non-Prismatic Beams with Multiple Rectangular Openings Monotonically Loaded - Abdulkareem, B. F.; Izzet, A. F.; Oukaili, N. (Engineering, Technology & Applied Science Research, 2021)
The main objective of this paper is to study the behavior of Non-Prismatic Reinforced Concrete (NPRC) beams with and without rectangular openings either when exposed to fire or not. The experimental program involves casting and testing 9 NPRC beams divided into 3 main groups. These groups were categorized according to heating temperature (ambient temperature, 400°C, and 700°C), with each group containing 3 NPRC beams (solid beams and beams with 6 and 8 trapezoidal openings). For beams with similar geometry, increasing the burning temperature results in their deterioration as reflected in their increasing mid-span deflection throughout the fire exposure period and their residual deflection after cooling. Meanwhile, the existing openings situation was compounded. The burned NPRC beams were left to gradually cool down under ambient laboratory conditions, and afterward, they were loaded until failure. The influence of temperature on the residual ultimate load-carrying capacity of each beam was studied by comparing these beams with unburned reference beams. Increasing exposure temperature reduces the ultimate strength of solid NPRC beams exposed to temperatures of 400°C and 700°C by about 5.7% and 10.84% respectively. Meanwhile, NPRC beams with trapezoidal openings showed ultimate strength reductions of 21.13% and 32.8% (for beams with 8 openings) and 28% and 34.4% (for beams with 6 openings) under the same burning conditions. The excessive mid-span deflections for these three types of beams were 2%–30.8%, 1.33%–21.8%, and 1.5%–17.4% under the same burning conditions.